2008
DOI: 10.1007/s11999-008-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background of Nontraumatic Osteonecrosis of the Femoral Head in the Korean Population

Abstract: Major thrombophilic mutations have been identified as risk factors for nontraumatic osteonecrosis of the femoral head (ONFH) in Caucasians. We asked whether the genetic background of patients with ONFH in the Korean population was similar. We analyzed factor V G1691A mutation (factor V Leiden), prothrombin G20210A mutation, and methylenetetrahydrofolate reductase C677T and A1298C polymorphisms in 71 patients (53 men, 18 women) with ONFH. We classified these patients as 51 alcohol-induced, 18 idiopathic, one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 21 publications
4
60
0
Order By: Relevance
“…Two studies in which the study subjects included an Asian population and conformed to the included criteria were deleted as they observed no FVL mutation in cases or controls. Chang et al (22) suggested that the FVL mutation is not a genetic risk factor for ONFH in Asians, or at least in the Korean population, which was in agreement with findings by Sun et al (24). The results obtained by these authors were consistent with previous reports, which demonstrated the absence of FVL mutation in the Chinese and Korean populations (25,26).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Two studies in which the study subjects included an Asian population and conformed to the included criteria were deleted as they observed no FVL mutation in cases or controls. Chang et al (22) suggested that the FVL mutation is not a genetic risk factor for ONFH in Asians, or at least in the Korean population, which was in agreement with findings by Sun et al (24). The results obtained by these authors were consistent with previous reports, which demonstrated the absence of FVL mutation in the Chinese and Korean populations (25,26).…”
Section: Discussionsupporting
confidence: 87%
“…We were relatively conservative in selecting studies, which likely underestimated the alrealy identified association. Several articles investigating FVL met our criteria, but they were excluded as they could not provide sufficient information for calculating the ORs of the FVL mutation and be extracted (22)(23)(24). Consequently, the studies that were included in this meta-analysis strengthened the association between FVL mutation and ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…ONFH is one of the most common diseases of the hip in Korea, with higher incidence than that in other countries; it is responsible for more than half of the cases of total hip arthroplasty, whereas it is relatively rare in the Unites States [8]. In recent years, the clinical significance of ONFH in hip diseases has received much attention, but the details of its pathogenesis and epidemiology are not well understood; although it is generally assumed that venous thrombosis with blood flow obstruction to the femoral head, mediated by thrombophilia and/or hypofibrinolysis, is important in the development of ONFH [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the clinical significance of ONFH in hip diseases has received much attention, but the details of its pathogenesis and epidemiology are not well understood; although it is generally assumed that venous thrombosis with blood flow obstruction to the femoral head, mediated by thrombophilia and/or hypofibrinolysis, is important in the development of ONFH [17,18]. At the genetic level, some genes have previously been reported as risk factors for ONFH, including a G1691A mutation in factor V (factor V Leiden), a G20210A mutation in prothrombin, and polymorphisms in 5, 10-methylenetetrahydrofolate reductase (MTHFR; C677T and A1298C) [8,19,20]. The presence of these genetic variations is associated with a hypercoagulable state, and increases the risk of thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation